A ONLINE LABORATORY FOR EXCHANGE EXEMPLARY DIGITAL TRANSFORMATIONS AND ARTIFICIAL INTELLIGENCE MEANS (Isagoge - Journal of Humanities and Social Sciences, 2025)
In recent years, unprecedented global changes have occurred in the digital and traditional worlds, associated with a significant acceleration of the impact of digital transformations and artificial intelligence means as one of the main factors of evolutionary and revolutionary engines of modern civilization, which provides unprecedented opportunities, problems and challenges for everyone. One of the ways, methods, and means of promoting sustainable development of individuals is our Online Laboratory for the exchange of exemplary digital transformations and artificial intelligence means. The best strategy, long-term plan is the balanced implementation of personally-centric projects with the support of a powerful ecosystem and scientific and educational infrastructure of online management systems, online laboratories with online schools,master classes and smart simulators of environments, situations, scenarios, procedures.